Climatic control on stacking and connectivity of fluvial successions: Upper Cretaceous Bajo Barreal Formation of the Golfo San Jorge basin, Patagonia - Paredes, José M. (2020)
Fil: Paredes, José M. Universidad Nacional de la Patagonia San Juan Bosco. Chubut, Argentina.